Gametogenesis of Nypha Palm Worm Namalycastis rhodochorde (Polychaeta: Nereididae) - Junardi Junardi; Tri Rima Setyawati; Edy Yuwono (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2010)
The Nypha Palm Worm Namalycastis rhodochorde has been used as bait for fishing in Pontianak. Culturing the worm is one potential effort for its commercialization as well as to overcome the overexploitation of the worm which also brings about the degradation of its natural habitat. Samples of the worm were collected from mangrove forest area in Sungai Kakap, West Kalimantan. Fresh sample of gametes from coelomic fluid were observed carefully under compound microscope to determine phase of gamete development. Oogenesis consisted of three consecutive stages namely immature, submature, and mature with ≤40 μm, 40<x<120 μm, and ≥120 μm in diameter, respectively. The spermatogenesis phases consisted of, spermatogonia, spermatid tetrad and spermatozoa.